Analogi Praktek Zina dan Dating App Menurut Islam - Eka Danis Saputri; Tiara Vania Wijaya Putri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to explore Islamic views on the use of dating apps in the context of the potential for adultery practices, while the Qur'an expressly prohibits adultery practices and emphasizes the need to maintain views and behavior.The research method used is qualitative library with a description approach, the primary data is the datig app which will focus on Islamic studies through the Qur'an and Hadith. While the data collection is by data reduction, presentation, and conclusion. The results of this study indicate that the phenomenon of increased downloading and use of dating apps among the community does not necessarily lead to dating app abuse. Because public knowledge about religion in addressing the use of dating apps is still actively involved by the community. The cause and effect arises as a result of the community's inability to utilize the dating app. So that it has an impact on social boundaries. So it is necessary to encourage a deeper understanding of Islamic teachings in the context of technology, as well as provide insight into how Muslim communities can face technological developments by maintaining religious values and morality